دور منظمات المجتمع المدني في ترسيخ قيم الديمقراطية في الجزائري - بلاعدة بلال - زلاقي مراد (جامعة المسيلة, 2024)
Consolidatingdemocratic values in society ensures the contribution and participation of citizens in the decision-makingprocessrelated to their public affairs. Among the most important mechanisms for activatingthis participation isenhancing the role of civil society organizations in adopting and presentingcitizens’ concerns, contributing to enactinglawsregulatingtheirlives, drawing up public policies, and determining the extent of theirembodiment on the ground. Algeriaisconsideredamong the countries that have tried to adoptthisapproachwithin the framework of its initiative aimedat building a democratic society and embodyingit in laws and constitutions that have worked to enable civil society organizations to contribute to the management of public affairs to consolidatedemocratic values. This isevident by givingher the opportunity to express her opinion and presentherconcerns to the legislative institution This iswhywefindthat civil society organizations in Algeriaplayed an important role in consolidatingdemocratic values, throughencouragingpolitical participation. Oversight, accountability, and defense of humanrights as an important actor in establishing the principles of good governance. Itsmembership in election monitoring committees and encouragingcitizens to participate in local councils in order to consolidateparticipatorydemocracy. And implementingdevelopmentprojectsaimedatimproving living conditions to achieve effective local development. In general, civil society organizations in Algeriacanbeconsidered to have achievedsomesuccesses in consolidatingdemocratic values despite the many obstacles they face. As theseorganizations continue to work and developtheirstrategies, theycancontributesignificantly to achieving a more comprehensive and justdemocratic society. In order to achievegreaterprogress, the existing challenges and obstacles must beaddressedthroughlegal and politicalreforms and increasedfinancial and technical support for theseorganizations.
Keywords: civil society organizations. Democracy. Algeria